Pemanfataan Sensor Proximity Untuk Kran Wudhu Otomatis Pada Mesjid Negeri Larike - Connie E Pelamonia; Rina Latuconsina; Zuleiha M. Masahida; Sylvia Irene Persulessy; Indra Wahyudi (Jurnal Aplikasi Dan Inovasi Ipteks "SOLIDITAS", 2023)
Larike country, one of the traditional villages located on Ambon Island and is part of the West Leihitu District, Central Maluku Regency. Larike Country has several unique and interesting tourist areas such as: Batu Layar, Pancoran Kuning, Morea Pond Tour and others, there are several tourist spots that attract the attention of local and foreign tourists to visit Larike Country.The pandemic that has hit the world in the last 3 years requires us to always live healthy both for ourselves and for others. We will be in a new normal condition where we will make new habits in social interaction. The new habits include: always wearing a mask, washing hands before and after doing something especially when in public places, keeping a distance and reducing activities on the spot.The use of the ablution faucet at the Larike mosque still uses a manual faucet that directly touches the faucet and is used by many people. To anticipate the spread of the virus, the use of automatic tools which are appropriate technology, such as the use of automatic faucets in places of worship.